LIQUIDATION OF OBJECTS ON WHICH THE RIGHT FOR SEPARATE SATISFACTION EXISTS - Jelena Čuveljak; Petra Božić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The goal of the bankruptcy procedure is to satisfy the creditors of the bankrupt debtor, and today most of the assets are objects on which the right for separate satisfaction exists, therefore the method of liquidation of objects is of crucial importance for achieving the goal of the bankruptcy procedure. The electronic public auction was introduced as a way of liquidation of objects on which the right for separate satisfaction exists in bankruptcy proceedings with the aim of solving existing problems and enabling creditors to cash in more favourably, but in practice numerous problems arose, which is why these rules have been changed several times, but still certain problems are observed in practice. Therefore, the authors analyze the rules on electronic public auctions, referring to problems that have arisen in practice, and suggest possible solutions.